Problems With Section Two ITP TOEFL Test - Rizki Ananda (Universitas Syiah Kuala, 2016)
This study was designed to investigate (1) the difficulties faced by EFL university students with section two of the ITP, and (2) whether part A or part B was more difficult for them and why. A number of 26 students from two different universities, Syiah Kuala University and the State Islamic University Ar-Raniry were the samples for the test. The data was obtained from a multiple choice questionnaire test consisting of 46 questions, each with 4 answers to choose from. The results showed that inversions (12%), subject-verb agreements (10%), adverb clause connectors (7%), passives (6%), reduced adjective clauses (5%), parallel structures (5%) and use of verbs (5%) were the most difficult questions for the students. Furthermore, they felt that part B was more difficult than part A, as finding an error in a sentence was harder than completing a sentence from a multiple choice. Furthermore, the length of questions in part A did not affect the amount of time the students spent to complete part A and did not cause them to panic. Also, unfamiliar words in part A were not regarded as a problem by the students. Hence, TOEFL teachers and trainers are highly encouraged to pay more attention to doing study exercises for the seven topics with the highest percentages above in part A and also to more practice for part B.